„Słowa są jak bezrobotni”. Kilka wstępnych uwag na temat ekonomicznych paradoksów języka awangardy - Skurtys, Jakub (Zagadnienia Rodzajów Literackich, 2019)
The paper is an attempt to outline a few problems connected with economic modes of reading the historic avant-garde, mainly its poetry. The author recapitulates a short history of its studies based on symbolic economies in order to consider possible semantic differences, resulting in the various uses of economic analogy in the discourse of the first avant-garde. The article focuses on Futurist and Constructivists movements, trying to sketch conflicts between political commitment and artistic autonomy, possible economies of sign and some sources of the “economic imagination”.